Verotoxigenic Escherichia coli (Vtec): A Major Public Health Threat in Canada - David L Woodward; Clifford G Clark; Richard A Caldeira; Rafiq Ahmed; Frank G Rodgers (Canadian Journal of Infectious Diseases)
BACKGROUND: Verotoxigenic Escherichia coli (VTEC) was first described in Canada during the 1980s as an emerging foodborne disease in association with morbidity and mortality in outbreaks of hemorrhagic colitis caused by E coli O157:H7.